2018
DOI: 10.1002/jcb.27359
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide inhibits hypoxia‐induced impairment of human RBC deformability through reducing the cross‐linking of membrane protein band 3

Abstract: NO may prevent decreased of RBCs deformability through reducing the cross-linking of membrane band 3 under hypoxia; this helps microvascular perfusion of RBCs during ischemic and hypoxic disease states.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 71 publications
(155 reference statements)
0
8
0
Order By: Relevance
“…These biochemistry modifications were contributing to alterations on RBC deformability. NO may prevent these modifications ( 23 ). However, observations on RBC rheology from animal models must be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
“…These biochemistry modifications were contributing to alterations on RBC deformability. NO may prevent these modifications ( 23 ). However, observations on RBC rheology from animal models must be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
“…RBCs are permanently in danger of oxidative stress across their lifetime due to the high cellular concentration of oxygen and Hb [ 49 , 50 ]. It also leads to a series of changes, such as crosslinking of membrane protein, reduction of deformability, and release of MetHb, which further aggravates the free radical burst and causing secondary damage to the body [ 51 53 ]. In this study, we also found that oxidative stress induced membrane protein crosslinking and the presence of dysmorphic RBCs under in vitro oxidation conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The lipid composition in the RBC membrane including cholesterol, sphingomyelin and phosphatidylcholine is reduced in diabetes mellitus 2 patients (T2D) (2). It also suppresses tyrosine phosphorylation of band 3 phosphorylation under hypoxic conditions (51).…”
Section: Sem Analysis Of Stressed Rbcs and Recovery By 8 Bromo-cgmpmentioning
confidence: 99%